Articular Syndrome Characteristics in Children with Mucopolysaccharidosis Type I - Nato D. Vashakmadze; Mikhail M. Kostik; Nataliya V. Zhurkova; Nataliya V. Buchinskaia; Ekaterina Yu. Zakharova; Margarita A. Soloshenko ("Paediatrician" Publishers LLC, 2021)
Background. Mucopolysaccharidosis type I is disease from the group of lysosomal storage disease developing due to mutations in the IDUA gene. It leads to the accumulation of glycosaminoglycans (GAGs) in organs and tissues. Joints damage in this disease is systemic and progressive.Objective. The aim of the study. Nowadays, relevant issue is to investigate the effects of various types of pathogenetic therapy on the state of the osteoarticular system in patients with severe and mild phenotypes of MPS I to prevent further progression of joint pathology.Methods. The study included 46 patients diagnosed with "mucopolysaccharidosis type I". 35 children had severe phenotype (Hurler syndrome) and 11 - with mild phenotypes (Hurler-Scheie and Scheie syndromes). The onset age of clinical manifestations in osteoarticular system, the state of large and small joints, and the presence of cervical stenosis according to the therapy were evaluated in these patients.Results. The osteoarticular system pathology can be usually revealed in all patients with MPS I, in both mild and severe phenotypes. The contractures of shoulder, ulnar, wrist, and small hand joints have been revealed in most patients with Hurler syndrome, regardless of the administered therapy. Hip joints pathology was observed in children who was administered with: enzyme replacement therapy (ERT) - in 46.7% of cases, hematopoietic stem cell transplantation (HSCT) in combination with ERT - in 34.4% of cases. Patients with Hurler syndrome administered with HSCT in combination with ERT had cervical stenosis statistically significantly more rarely (p = 0.018) compared to patients treated with ERT only. Patients with Hurler syndrome who were on ERT had statistically significantly lower growth rates than patients after HSCT in combination with ERT. Lesions in ulnar, wrist, knee and small hand joints were the most common in children with mild phenotypes (in 90% of cases).Conclusion. Combined therapy (HSCT and ERT) in patients with Hurler syndrome reduces severe manifestations in osteoarticular system, including children with a pathogenic nucleotide variant c.208C>T in a homozygous state.